(Not) Dancing Together : Monetary Policy Stance and the Government Spending Multiplier - Belinga, Vincent (IMF Working Papers; Working Paper, 2015)
This paper provides estimates of the government spending multiplier over the monetary policy cycle. We identify government spending shocks as forecast errors of the growth rate of government spending from the Survey of Professional Forecasters (SPF) and from the Greenbook record. The state of monetary policy is inferred from the deviation of the U.S. Fed funds rate from the target rate, using a smooth transition function. Applying the local projections method to quarterly U.S. data, we find that the federal government spending multiplier is substantially higher under accommodative than non-accommodative monetary policy. Our estimations also suggest that federal government spending may crowd-in or crowd-out private consumption, depending on the extent of monetary policy accommodation. The latter result reconciles-in a unified framework-apparently contradictory findings in the literature. We discuss the implications of our findings for the ongoing normalization of monetary conditions in advanced economies.